Effect of whole-plant mulberry supplementation on testis development and antioxidant capacity in Hu rams - Jiamei Liu; Ziwei Liang; Wanhong Li; Xiuxiu Weng; Xiangpeng Yue; Fadi Li (Animal Bioscience)
Objective This study investigated the effects of dietary whole-plant mulberry (WM) on testicular development and antioxidant performance in sheep. Methods Fifty-four three-month-old Hu sheep were divided into three groups and fed diets containing different proportions of WM (WM0, without WM; WM4, 4% WM; WM8, 8% WM). Following a 70-day feeding trial, 15 individuals from each group were humanely slaughtered. The total cholesterol (T-CHO) levels and antioxidant capacity of the testes were measured. The expression of functional genes was assessed by reverse transcription quantitative polymerase chain reaction. Leydig cells treated with proanthocyanidins (PCs) at concentrations of 0, 5, 10, and 20 μM. The total antioxidant capacity level (T-AOC), testosterone (T) level, cell viability, apoptosis and necrosis ratio were assessed. RNA sequencing analysis was performed to identify the differentially expressed genes (DEGs) between the control (CK) and 10 μM PC groups. Results The PCs content in the WM was measured at 56.93±2.146 mg/g. The total (p = 0.06), the left (p = 0.07). and the right (p<0.05) testicular weights were increased in the WM8 group compared to the WM0 group. Compared to the WM0 group, the WM8 group showed decreased T-CHO (p<0.05) and increased T-AOC (p<0.05) in the testis, and the expression of StAR, PPARγ and Bcl2 was significantly increased (p<0.05), while Caspase9 and Caspase3 were significantly decreased (p<0.05). In vitro, supplementation of 10 μM PCs in Leydig cells significantly increased cell viability, T-AOC and T levels, and reduced the necrosis ratio (p<0.05) compared to the CK group. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis showed that the DEGs were significantly enriched in the steroid biosynthesis pathway, p53 signaling pathway, cholesterol metabolism, PPAR signaling pathway, and Hippo signaling pathway. Conclusion Supplementation with 8% WM improved antioxidant capacity and stimulated testis development through the promotion of cell proliferation, T synthesis, and antioxidant capacity of Leydig cells.